AngioSuite-Assisted Volume Calculation and Coil Use Prediction in the Endovascular Treatment of Tiny Volume Intracranial Aneurysms. (29th July 2021) - Du, Zhihua; Lv, Bin; Cao, Xiangyu; Liu, Xinfeng; Zhang, Rongju; Su, Hui; Wang, Jun
Abstract : Background and Purpose . Ruptured tiny volume intracranial aneurysms (TVIAs) are associated with high risk of intraprocedural perforation. Aneurysm volume measuring is important for treatment planning and packing density calculation. We aim to assess the ability of the AngioSuite software in calculating TVIAs and guiding the selection of suitable coil. Methods . Thirty-three consecutive patients with 34 TVIAs were prospectively recruited and treated with endovascular techniques. The volume of TVIAs and the required length of coils were calculated by the AngioSuite software before embolization. The treatment efficacy of TVIAs was assessed using the Raymond scale (Rs) and the modified Rankin scale (mRs). Results . Of the 34 aneurysms with an average volume of 7.16 mm 3, 13 aneurysms were treated with sole coil embolization, 19 by stent-assisted embolization, and 2 by balloon-assisted embolization. The average coil length was 5.32 cm, and the average packing density was 41.21%. The immediate DSA showed that total occlusion (Rs = 1 ) was achieved in 15 aneurysms, subtotal (Rs = 2 ) in 9, and partial (Rs = 3 ) in 11. Total occlusion was achieved in 30 aneurysms and subtotal in the other 4 aneurysms at 6-month follow-up. Baseline volume and diameter of aneurysms were significantly correlated with the coil length (r = 0.801, P < 0.001 ; r = 0.711, P < 0.001 ). Conclusions . Coil embolization of TVIAs was easy to achieve high packing density. According to the data from AngioSuite, relative few coils can increase the safety in procedure and stenting may reduce risk of aneurysmal recurrence.